Trade and welfare effects of the WTO Trade Facilitation Agreement - Cosimo Beverelli; Isabella Gourevich; Inga Heiland; Alexander Keck; Mario Larch; Yoto Yotov (World Trade Organization (WTO), 2023)
The WTO Trade Facilitation Agreement (TFA) has been predicted to bring about an expansion in trade flows and real income gains. To date, there is still very limited empirical evidence on the actual post-implementation impact of the TFA. This paper provides an assessment, combining econometric estimations from a structural gravity model with general equilibrium modelling results. The main insight is that the TFA increased trade, in particular in agriculture, between developing countries that made commitments. General equilibrium estimations indicate that agricultural trade increases by 5% worldwide, while total trade increases by 1.17% worldwide as a result of TFA implementation. Trade gains accrue in particular to LDCs, whose exports increase by 2.4% overall (17% in agriculture). Furthermore, as a result of TFA implementation, real income increases by 0.12% worldwide (0.24% for LDCs).
Keywords: F13; F14; F17; 330; Trade facilitation; Structural gravity; CGE models